DINAMIKA SUMBER-SUMBER KEKUASAAN DALAM PEMILIHAN KEPALA DESA: DARI MITOS MENUJU PERTUKARAN SOSIAL - Ciptono, Ciptono (Universitas Wijaya Kusuma Surabaya, 2025)
Village head elections in Indonesia have a long history, compared to regional head elections. The purpose of this study is to describe the use of sources of power by candidates in village head elections in Sumberarum Village from time to time. The research method is a longitudinal method with a research period starting from the 1999 Pilkades to 2019. Data were collected through documentation studies, in-depth interviews, and observations. The research periodization focused on the leadership period of the Kromo Baru lineage, the end of the Kromo Baru lineage oligarchy, and the election of the Sumberarum village head from outside the Sambong lineage. The results of the study show that the survival of village heads from the Kromo Baru lineage for more than 1 century is due to the existence of myths that were developed to maintain power at the village level. The survival of the Kromo Baru lineage dynasty in leadership in Sumberarum Village is due to genealogical, cultural and sociological factors. Genealogical factors, the Sumberarum village head was led by Kromo Baru (1902) to Muniroh (2013-2019) who were one relative. Cultural factors can be observed from the development of myths and the sacralization of heirlooms, such as ageman, keris, thontongan, and kimo gelung mbah Kromo Baru which are considered as a means of maintaining power. In addition to the sacralization of heirlooms, descendants of the Kromo Baru lineage who participate in the village head election also use 'smart people' or shamans. The collapse of the power of the Kromo Baru lineage was due to the failure and weakness of the female village head, the great-granddaughter-in-law of the Kromo Baru lineage, namely Muniroh. The emergence of the Sumberarum village head from outside the Kromo Baru lineage, marks the use of sources of power that no longer rely on myths that have developed for more than 1 century, but also use material sources of power. The use of material sources such as providing basic necessities, money, t-shirts, and money, marks a shift in voter behavior that is more rational and transactional.